A comprehensive guide to information security management and audit - Banoth, Rajkumar; Gugulothu, Narsimha; Godishala, Aruna Kranthi (Boca Raton : CRC Press, 2023)
"The book explores information security concepts and applications from an organizational information perspective and explains the process of audit planning and preparation. It further demonstrates audit techniques and collecting evidence to write important documentation by following the ISO 27001 standards"--
OCLC-licensed vendor bibliographic record.
Keywords: Confidential business information -- Security measures; Computer networks -- Security measures; Information audits; Computer security; TECHNOLOGY / Telecommunications; COMPUTERS / Computer Engineering; TECHNOLOGY / Electronics / General